2003
DOI: 10.1038/nature02224
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Möbius aromatic hydrocarbon

Abstract: The defining feature of aromatic hydrocarbon compounds is a cyclic molecular structure stabilized by the delocalization of pi electrons that, according to the Hückel rule, need to total 4n + 2 (n = 1,2, em leader ); cyclic compounds with 4n pi electrons are antiaromatic and unstable. But in 1964, Heilbronner predicted on purely theoretical grounds that cyclic molecules with the topology of a Möbius band--a ring constructed by joining the ends of a rectangular strip after having given one end half a twist--shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
390
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(416 citation statements)
references
References 24 publications
5
390
0
7
Order By: Relevance
“…44,47 It was found that mean-field Hubbard treatment of Coulomb interactions gives a minimal spin polarization and an associated magnetic domain wall, 42,43 whereas density functional calculations predict finite total magnetization. 44,47 On the experimental side, although we are not aware of Möbius graphene nanoribbons with zigzag edges yet, twisted nanoribbons were recently obtained inside carbon nanotubes through electron irradiation of functionalized fullerenes 36 and a stable Möbius aromatic hydrocarbon was synthesized by Ajami et al 41 In this work we describe the effect of Möbius topology on the one-electron properties of graphene nanoribbon rings as a function of the number of carbon chains, both even and odd. We compare the Möbius topological insulator with normal insulators, cylindrical graphene nanoribbon rings with cyclic boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,47 It was found that mean-field Hubbard treatment of Coulomb interactions gives a minimal spin polarization and an associated magnetic domain wall, 42,43 whereas density functional calculations predict finite total magnetization. 44,47 On the experimental side, although we are not aware of Möbius graphene nanoribbons with zigzag edges yet, twisted nanoribbons were recently obtained inside carbon nanotubes through electron irradiation of functionalized fullerenes 36 and a stable Möbius aromatic hydrocarbon was synthesized by Ajami et al 41 In this work we describe the effect of Möbius topology on the one-electron properties of graphene nanoribbon rings as a function of the number of carbon chains, both even and odd. We compare the Möbius topological insulator with normal insulators, cylindrical graphene nanoribbon rings with cyclic boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…10 Interestingly, it has been suggested that nontrivial properties of graphene nanoribbons can be generated directly by engineering a nontrivial Möbius geometry of the nanoribbon without the need for the spin-orbit coupling. [40][41][42][43][44][45][46][47][48][49][50][51] For example, it was shown by Guo et al 46 that one electron states of a class of Möbius graphene ribbons with zigzag edges can be understood by introducing a non-Abelian gauge field 46 as in topological insulators. [6][7][8][9][10][11][12] However, these authors used the s orbitals instead of p z orbitals as the basis needed to describe graphene nanoribbons and limited their work to an even number of atomic chains.…”
Section: Introductionmentioning
confidence: 99%
“…Möbius aromaticity 1,2 has revolutionized the chemistry of expanded porphyrins. Sessler and Seidel 3 defined expanded porphyrins as "synthetic analogues of the porphyrins, and differ from these and other naturally occurring tetrapyrrolic macrocycles by containing a larger central core with a minimum of 17 atoms, while retaining the extended conjugation features that are a hallmark of these quintessential biological pigments."…”
Section: Introductionmentioning
confidence: 99%
“…In view of the diverse range of possible functions of p-conjugated molecules, the current method has the potential to open up a new era of 3D p-conjugated molecules. Interestingly, as the structure of 3 is topologically identical to a Reuleaux triangle, the extension of this synthetic strategy should make it possible to synthesize molecules with Klein's quartic curve structure 38 , a 3D version of a Möbius strip 39 .…”
Section: Discussionmentioning
confidence: 99%